2023
DOI: 10.3390/life13020423
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiles of Human HaCaT Cells in Response to Gynostemma pentaphyllum Extracts Obtained Using Three Independent Methods by RNA Sequencing

Abstract: Gynostemma pentaphyllum (GP) is widely used in herbal medicine. In this study, we developed a method for the large-scale production of GP cells using plant tissue culture techniques combined with bioreactors. Six metabolites (uridine, adenosine, guanosine, tyrosine, phenylalanine, and tryptophan) were identified in GP extracts. Transcriptome analyses of HaCaT cells treated with GP extracts using three independent methods were conducted. Most differentially expressed genes (DEGs) from the GP-all condition (comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Thanks to the rapid development of high-throughput sequencing and bioinformatic tools, it is now possible to examine the effects of plant extracts on specific human cell lines [ 12 ]. Several previous studies have demonstrated the usefulness of RNA sequencing in identifying human RNAs regulated by a specific plant extract [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the rapid development of high-throughput sequencing and bioinformatic tools, it is now possible to examine the effects of plant extracts on specific human cell lines [ 12 ]. Several previous studies have demonstrated the usefulness of RNA sequencing in identifying human RNAs regulated by a specific plant extract [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%